2011
DOI: 10.1111/j.1745-4565.2011.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Antibiotic Susceptibility Profiles of Staphylococcus Aureus and Bacillus Cereus Strains Isolated From Biltong

Abstract: Biltong, an intermediate moisture meat product from South Africa, has been regarded as microbially safe because of its low water activity, low pH as well as the presence of curing salts. However, in this study, Staphylococcus aureus and Bacillus cereus counts from the biltong samples, in most cases, were above the infective dose limit and the South African national guidelines. Antimicrobial resistance of S. aureus and B. cereus on selected antibiotics was determined. Both species (S. aureus and B. cereus) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 62 publications
3
10
1
Order By: Relevance
“…S. aureus was detected only in the study of Naidoo & Lindsay (2010a) with three strains of the 159 Staphylococcus isolates being confirmed as S. aureus. Another study showed that S. aureus in most biltong sampled exceeded 100 cfu.g -1 (Shale & Malebo, 2011). In South Africa, the commercial biltong industry uses the microbiological requirements as stated in the South African National Standards (SANS) 885.…”
Section: Microbial Quality and Shelf-life Of Biltongmentioning
confidence: 99%
“…S. aureus was detected only in the study of Naidoo & Lindsay (2010a) with three strains of the 159 Staphylococcus isolates being confirmed as S. aureus. Another study showed that S. aureus in most biltong sampled exceeded 100 cfu.g -1 (Shale & Malebo, 2011). In South Africa, the commercial biltong industry uses the microbiological requirements as stated in the South African National Standards (SANS) 885.…”
Section: Microbial Quality and Shelf-life Of Biltongmentioning
confidence: 99%
“…The information concerning the microbiological quality of traditional cured meat products available in scientific literature is not always satisfactory. The results of studies on the presence of various pathogens in traditional cured meat products obtained by authors from different countries confirm that products of that type may sometimes be the cause of serious diseases in humans (Abrahim et al, 1998;Moore, 2004;Chevallier et al, 2006;Ferreira et al, 2006;Ferreira et al, 2007;Gounadaki et al, 2008;Mhlambi et al, 2010;Naidoo and Lindsay, 2010;Shale and Malebo, 2011;Rajkovic, 2012).…”
Section: Introductionmentioning
confidence: 72%
“…Products manufactured by applying traditional methods are frequently ready to eat (RTE) products that may represent a significant source of pathogens dangerous for health (Abrahim et al, 1998;Moore, 2004;Chevallier et al, 2006;Ferreira et al, 2006;Ferreira et al, 2007;Gounadaki et al, 2008;Mhlambi et al, 2010;Naidoo and Lindsay, 2010;Shale and Malebo, 2011;Rajkovic, 2012). Differences in the processing methods applied during production of traditional cured meat products may determine the differences in the final product quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The six isolates were resistant to 30 µg of nalidixic acid. Previous studies have shown that 105 strains of Enterococcus and certain specific strains of Bacillus are resistant to this antibiotic [23].…”
Section: Resultsmentioning
confidence: 99%